2001
DOI: 10.1159/000050601
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Mutation of p53 in Tumor Effusion Cells of Patients with Ovarian Carcinoma: Response to Cisplatin-Based Chemotherapy

Abstract: p53 alterations are considered as one of the most important factors responsible for drug resistance in ovarian carcinomas, although the relationship between p53 gene status and response to cisplatin-based chemotherapy in ovarian cancer patients remains unclear. The aim of the study was to evaluate the relationship between p53 protein accumulation, p53 gene mutation and response to cisplatin-based chemotherapy in patients with ovarian carcinoma considering conventional clinicopathological parameters. Tissue sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Our findings are consistent with studies showing an association between p53 overexpression and PFS (16,22) or tumor grade (12,13,15,16,17,19,2224,26,32,33,35,37,40,42) and with studies demonstrating that p53 overexpression was not associated with PFS (10,17,30,33,35,38,41,42), OS (8,10,11,17,24,25,29,30,3239,41,42), tumor response (16,23,25,26,30,37,3942), or disease status (12, 27), and that p53 was not an independent prognostic factor for PFS (16,17,34,35,42) or OS (12,14,16,17,19,22,24,29,32,33,35,39,40,42) in invasive EOC. However, these results contradict studies demonstrating that p53 overexpression was associated with OS (12,13,15,16,19,20,22,23,27,28,40), and/or tumor response (18,22), and that p53 was an independent prognostic factor for PFS (22) or OS (15,20,23,27,28,31) in invasive EOC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with studies showing an association between p53 overexpression and PFS (16,22) or tumor grade (12,13,15,16,17,19,2224,26,32,33,35,37,40,42) and with studies demonstrating that p53 overexpression was not associated with PFS (10,17,30,33,35,38,41,42), OS (8,10,11,17,24,25,29,30,3239,41,42), tumor response (16,23,25,26,30,37,3942), or disease status (12, 27), and that p53 was not an independent prognostic factor for PFS (16,17,34,35,42) or OS (12,14,16,17,19,22,24,29,32,33,35,39,40,42) in invasive EOC. However, these results contradict studies demonstrating that p53 overexpression was associated with OS (12,13,15,16,19,20,22,23,27,28,40), and/or tumor response (18,22), and that p53 was an independent prognostic factor for PFS (22) or OS (15,20,23,27,28,31) in invasive EOC.…”
Section: Discussionsupporting
confidence: 92%
“…Among the studies that examined OS as an end-point and used the N-terminal DO-7 antibody with different cut-points in FFPE or frozen tumor, most including ours showed that p53 overexpression was not associated with OS (14,24,30,32,33,34,39,42). In contrast, Ozalp and colleagues demonstrated that p53 overexpression categorized as negative or positive was associated with OS (27).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several other studies also confirmed p53 status relevance in predicting the efficacy of NSCLC patients' treatment in vivo (Nakanishi et al 1999;Rusch et al 1995;Kawasaki et al 1997;Brattstrom et al 1998;Tanaka et al 1999). Tissues without p53 accumulation showed significantly better in vitro sensitivity, and only in those patients was a good clinical response to cisplatin-based chemo(thermo)therapy observed, in agreement with in vitro results (Higashiyama et al 2000); similar results were frequently observed in tumors of various origins (e.g., in ovarian cancer, Bar et al 2001). p53 gene status modulates the extent of chemosensitivity and the induction of apoptosis by different anticancer agents in NSCLC cells (Perdomo et al 1998;Lai et al 2000).…”
Section: Discussionsupporting
confidence: 68%
“…Four publications were identified that explored the relationship of p53 and residual disease, of which two found a significant association with p53 protein overexpression and suboptimal debulking in univariate analysis ( n =82, P =0.01) (Dogan et al , 2005) ( n =83, P <0.041) (Geisler et al , 1997), one demonstrated a trend to overexpression and suboptimal debulking ( n =136, P =0.07) (Ferrandina et al , 1999) and one did not find a significant association ( n =79, P =0.36) (Bar et al , 2001). These four studies used heterogeneous histological samples, variable clinical stages and varying definitions of suboptimal and optimal debulking.…”
Section: Resultsmentioning
confidence: 98%